Distinct feedback actions of behavioural arousal to the master circadian clock in nocturnal and diurnal mammals. (April 2021) - Jha, Pawan Kumar; Bouâouda, Hanan; Kalsbeek, Andries; Challet, Etienne
Highlights: Behavioural arousal affects circadian rhythms in mammals by its feedback action on the master clock in the suprachiasmatic nucleus (SCN). In nocturnal animal, arousing stimuli in the middle of the rest period induces a phase advance and attenuate light-induced phase-shifts. The feedback of behavioural arousal to the SCN utilizes a network of connections involving several brain nuclei and neurotransmitters. Different responses to behavioural arousal between diurnal and nocturnal species, indicates distinct circadian windows of sensitivity to arousal. It is imperative to understand this disparity before addressing the question of therapeutic interventions to repair circadian misalignments. Abstract: The master clock in the suprachiasmatic nucleus (SCN) of the hypothalamus provides a temporal pattern of sleep and wake that - like many other behavioural and physiological rhythms - is oppositely phased in nocturnal and diurnal animals. The SCN primarily uses environmental light, perceived through the retina, to synchronize its endogenous circadian rhythms with the exact 24 h light/dark cycle of the outside world. The light responsiveness of the SCN is maximal during the night in both nocturnal and diurnal species. Behavioural arousal during the resting period not only perturbs sleep homeostasis, but also acts as a potent non-photic synchronizing cue. The feedback action of arousal on the SCN is mediated by processes involving several brain nuclei and neurotransmitters, which ultimately change the molecular functions of SCN pacemaker cells. Arousing stimuli during the sleeping period differentially affect the circadian system of nocturnal and diurnal species, as evidenced by the different circadian windows of sensitivity to behavioural arousal. In addition, arousing stimuli reduce and increase light resetting in nocturnal and diurnal species, respectively. It is important to address further question of circadian impairments associated with shift work and trans-meridian travel not only in the standard nocturnal laboratory animals but also in diurnal animal models.